KAJIAN SEDIMENT DELIVERY RATIO UNTUK DAERAH TANGKAPAN HUJAN WADUK SERMO KABUPATEN KULON PROGO, DAERAH ISTIMEWA YOGYAKARTA - NIFEN, SILTA YULAN ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Erosion will affect the area in the lower reaches of the river as a reservoir or lake. Erosion has accumulated in the reservoir will be sediment. To predict the outcome of sediment in the reservoir can use Sediment Delivery Ratio. Equation SDR (Sediment Delivery Ratio) has been developed in the United States that need to be examined how much can be used in Indonesia, especially Catchment Rain (DTH) Sermo Reservoir. MUSLE method (Modified Universal Soil Loss Equation) using software Arc.GIS 10.1. as well as the software ENVI 4.5. SDR value is calculated from the measurement results of data echosounding and existing empirical equations. From the results obtained by analysis of the rate erosion in DTH Sermo Reservoir is 6,97 mm/year or 125,51 tons/ha/year. The actual SDR value obtained by 0,765 or 76,5%. SDR equation estimates the most appropriate for DTH Sermo Reservoir is the equation (3.22) which was made by William (1977), because of the similarity is the watershed area, the slope of the basin, Indeks SCN CN gained SDR value approaching is 0,926 with a percentage difference of 21%. Key Word : Erosion, MUSLE , Sediment Delivery Ratio (SDR)